A case study of a business process reengineering project, 'Straightening the path for patients', at Taranaki Healthcare, a New Zealand Crown Health Enterprise, 1995-1997 : a thesis presented in partial fulfillment of the requirements for the degree of Master of Business Studies (Health Management) at Massey University - Pike, Pieter Wessel (Massey University, 1997)
This case study describes and analyses the Change lmperative(Phase One); Visioning (Phase Two); Redesign (Phase Three) and Plan for Implementation (Phase Four) Phases of a Business Process Reengineering (BPR) project in the New Zealand Health sector at Taranaki Healthcare. The research strategy in the words of Yin (1994, p.1) was "an empirical inquiry that investigates a contemporary phenomenon in its real life context" when the boundaries between phenomena and context are not clearly evident and in which multiple sources of evidence are used. Michael Hammer, president of Hammer and Co., Cambridge, first coined the term Business Process Reengineering, in 1990. He described reengineering as fundamental and radical redesign of business processes to achieve dramatic improvements. The application of BPR methodology, as change strategy, is now widely applied. Numerous studies concentrate on the methodology but few discuss its actual application in a real time project. This case study addresses this issue. The empirical part of this study involved two surveys together with a qualitative analysis of debriefing sessions held at the end of each phase. The first survey was conducted in July 1996, after the completion of the Visioning Phase and the second during November 1996, after the Plan for implementation Phase. Both surveys included a cluster sampling of the reengineering project team and a stratified random sampling of Taranaki Healthcare employees. The data collection was based on a multi-method approach and included a review of project reports, surveys before the project, and quantitative analysis of patient numbers, case complexity, capacity, utilisation and other demand management factors.
Keywords: Taranaki Healthcare administration; Reengineering (Management); Health services administration; New Zealand health sector